A study on soil engineering compositions of tropical residual soils of Peninsular Malaysia / Khairul Nizar Mohd Yusof and Lee Cheong Lun - Mohd Yusof, Khairul Nizar; Lee, Cheong Lun (2006)
Malaysia is situated at the equator line where the tropical climate existing the tropical residual soils and received average rainfall between 1778 mm to 3659 mm. Soil erosion and slope instability have lately become very serious problem in the tropical region. Therefore many researches from the various government and the private agencies had been studied regarding the soil erosion issues. Meanwhile, the objectives of the study are to determine the soil engineering composition of tropical residual soils at central and southern Peninsular Malaysia, There are 10 undisturbed samples taken at shallow depth (≤0.5 m) and all tests had been conducted at the Geotechnical Laboratory, Fakulti Kejuruteraan Awam dan Alam Sekitar (FKAAS), Kolej Universiti Teknologi Tun Hussein Onn. The soil particles from tested samples show 3.15 % to 12.77 % of clay. 50.81 % to 88.3 % of silt, and 0.15 % to 44.9 % of sand. The natural moisture content, w is in the range of 13 % to 38 % .The specific gravity, Gs, values are found to be in the range between 2.3 and 2.89. Plastic limit, w is in the range of 18 % and 37.47 %. While liquid limit. w values in between 33.6 % and 50 % and the plasticity index, I is in range of 11 % to 23.9 %. The results show that the w values are influenced by the percentage of clay. High percentage of moisture content values can restore more water than soil which has lower percent of clay. While lower percent of clay can generate lower values of I. The generated correlations will become a reference to the geotechnical design and adding information on potential future in the study area. This indication can assist engineers to the better understanding of the soil engineering compositions and also can predict the possible properties of destruction and loss of life that could be encountered.